2001
DOI: 10.1111/j.1749-6632.2001.tb05846.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow and Heat Transfer Predictions for Film Cooling

Abstract: Film cooling flows are characterized by a row of jets injected at an angle from the blade surface or endwalls into the heated crossflow. The resulting flowfield is quite complex, and accurate predictions of the flow and heat transfer have been difficult to obtain, particularly in the near field of the injected jet. The flowfield is characterized by a spectrum of vortical structures including the dominant kidney vortex, the horse‐shoe vortex, the wake vortices and the shear layer vortices. These anisotropic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(44 citation statements)
references
References 35 publications
1
39
0
Order By: Relevance
“…Also, the jet structure is dominated by a pair of kidney-shaped counterrotating vortex pair (CRVP). The shearing between the jet and the cross flow and the vorticity issuing from the jet exit have been attributed to be the main sources of the CRVP [5]. Since the coherent structures significantly affect the jet-into-cross flow hydrodynamics, the numerical approaches used should be able to resolve the large scale coherent dynamics.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Also, the jet structure is dominated by a pair of kidney-shaped counterrotating vortex pair (CRVP). The shearing between the jet and the cross flow and the vorticity issuing from the jet exit have been attributed to be the main sources of the CRVP [5]. Since the coherent structures significantly affect the jet-into-cross flow hydrodynamics, the numerical approaches used should be able to resolve the large scale coherent dynamics.…”
Section: Introductionmentioning
confidence: 98%
“…Acharya et al [5] investigated the film cooling of a jet into a cross flow, using different numerical approaches, namely, direct numerical simulation (DNS), large eddy simulation (LES), and several different turbulence models namely k −ε models and the Reynolds stress transport models (RSTM). They reported that the two-equation model usually underpredicts the lateral spreading of the film cooling jet and overpredicts its vertical penetration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, study of the jet flow in cross-flow is increasingly used for numerical simulation. In papers [18][19] the flow of the jet in cross-flow modeled with the help of Reynolds-averaged Navier-Stokes equations (RANS) and velocity field obtained numerical results are compared with experimental data. In papers [20][21][22] numerical simulation is perfomed by large eddy simulation (LES) method, which give much better results than the RANS approach.…”
Section: Introductionmentioning
confidence: 99%
“…A reacting transverse jet could affect the flame stabilization of a fuel jet issuing into a crossflow as a model of stack flares and also the secondary combustion zones in a gas turbine combustion chamber. On aspect of flow physics, Jet In Crossflow (JICF) has been regarded as a challenging test case for fundamental understanding of three-dimensional turbulent mixing and shear layer flows, thus it is often used for validating turbulent models by the fluid dynamics research community (Chochua et al, 2000;Acharya et al, 2001;Chassaing et al, 1974;Schluter and Schonfeld, 2000;Muppidi and Mahesh, 2007).…”
Section: Introductionmentioning
confidence: 99%